2018
DOI: 10.1002/esp.4379
|View full text |Cite
|
Sign up to set email alerts
|

Marine control over negative power law scaling of mass wasting events in chalk sea cliffs with implications for future recession under the UKCP09 medium emission scenario

Abstract: Coastal cliff erosion represents a significant geohazard for people and infrastructure. Forecasting future erosion rates is therefore of critical importance to ensuring the resiliency of coastal communities. We use high precision monitoring of chalk cliffs at Telscombe, UK to generate monthly mass movement inventories between August 2016 and July 2017. Frequency-magnitude analysis of our inventories demonstrate negative power law scaling over 7 orders of magnitude and, for the first time, we report statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…One of the challenges in the research is to foresee coastal evolution to ensure the resiliency of coastal communities (e.g. Gilham et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the challenges in the research is to foresee coastal evolution to ensure the resiliency of coastal communities (e.g. Gilham et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This research uses frequency densities, which provide an estimate of the production rate of each rockfall volume class, whilst the cumulative method provides a probabilistic hazard estimate of exceeding a given volumetric threshold. The method used for this research has previously been applied to the study of sea cliffs by Barlow et al (2012) and Gilham et al (2018).…”
Section: Negative Power Law Scaling Of Rockfallsmentioning
confidence: 99%
“…This is evidenced by the wedge failures at the site (Mortimore et al, 2004;Barlow et al, 2017) which constrain the magnitude of the observed larger failures in the inventory presented. Using these data, Gilham et al (2018) found that the power law scaling parameters (β and s) are correlated to Hs at Telscombe and developed a probabilistic recession model based on the UK Climate Change Projection (UKCP) 2009 medium emission scenario.…”
Section: Negative Power Law Scaling Parametersmentioning
confidence: 99%
“…Rockfall, or the removal of individual and superficial rocks from a cliff face [1,2], is a significant geohazard, particularly on coastal cliffs where the exposure of people and assets is often high [3,4]. Rock coasts account for much of the world's coastline [5], yet our understanding of their evolution remains limited by progressive time-dependent failure processes [6], geological and geometric settings [7][8][9], increasing environmental extremes [10,11], and the appropriateness of the available…”
Section: Introductionmentioning
confidence: 99%